COMPARATIVE STUDY OF STUDENTS' VISUAL-SPATIAL INTELLIGENCE IN GEOMETRY PROBLEMS FROM A GENDER PERSPECTIVE - Solihah, Silvi; Agustini, Rini; Hidayati, Santi Auliya (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This study aims to analyze visual-spatial intelligence in the subject of solid geometry from a gender perspective. The research employs a qualitative approach with a descriptive method. The subjects of this study were eighth-grade students at a public junior high school in Tasikmalaya City. The primary instrument of this research was a geometry test designed to measure visual-spatial intelligence through aspects such as imagination, conceptualization, problem-solving, and pattern recognition. The findings revealed significant differences between male and female students in visual-spatial intelligence. Male students demonstrated superior visual-spatial intelligence compared to female students, as evidenced by their better performance in the aspects of imagination, conceptualization, problem-solving, and pattern recognition. On the other hand, female students only excelled in conceptualization and problem-solving. The implications of this study suggest that gender-based differences in visual-spatial intelligence require special attention in the development of teaching methods that can help reduce this gap, particularly in areas that present challenges for female students.  Copyr All rights rese